P–343 Identification of circulating leukocyte microRNA–125b and microRNA–142–3p expression profiles in women with endometriosis before surgery and at 1 month after surgery. (6th August 2021) - Hocaoglu, M; Karacan, A; Locla. Karaalp, I; Yagiml. Ozturk, E; Kaynak, E; Demirer, S; Turgut, A; Tug, N; Komurc. Bayrak, E
Abstract: Study question: To investigate the expression profiles of microRNA–125b and micrpRNA–142–3p in women with endometriosis, compared with controls before surgery and at 1 month after surgery. Summary answer: The over-expression of miRNA–125b and miRNA–142–3p may be involved in the aetiopathogenesis of endometriosis which is related to systemic chronic inflammation. What is known already: Currently, there is no reliable non-invasive diagnostic biomarker for endometriosis. MicroRNAs (miRs) are small, non-coding RNAs that are involved in the post-transcriptional regulation of gene expression and promising biomarker candidates for noninvasive diagnosis of various diseases. Despite the small number of studies found that miRNA–125b and miRNA–142–3p have been associated with endometriosis, further evidence is therefore required from studies that examine these two miRNAs in diagnosis and even follow-up of women with endometriosis. Owing to endometriosis is a systemic chronic inflammatory disease, investigating these miRs in blood leukocytes of patients with endometriosis may illustrates the molecular mechanism of endometriosis. Study design, size, duration: This is a prospective longitudinal study performed between 2018 November and 2021 February. The sample size of 42 individuals of two groups were calculated considering the power analysis (α = 0.05) with Mann-Whitney U test (effect size, d=0.8) and were calculated as 80%. Women with endometriosis (n = 21) and surgically confirmed endometriosis-free women (n = 21) were included in the study. Laparoscopy and/or laparotomy was performed to determine the presence or absence of endometriosis. Participants/materials, setting, methods: Women aged 18–50 years were recruited from two tertiary hospital settings. Severity of endometriosis was assessed by the rASRM classification. Using real-time quantitative PCR, miRNA–125b and miRNA–142–3p in leukocyte were analyzed in women with endometriosis before surgery and at 1 month after surgery, compared to controls without endometriosis. The results were calculated as relative quantification values. The presumed targets of these two miRNAs were identified via 3 different target prediction algorithms:TargetScan, miRDB and DIANA-TarBase. Main results and the role of chance: There were no demographic discrepancies between groups. The relative expression of miRNA–125b and miRNA–142–3p were significantly higher in women with endometriosis than in control subjects before surgery (p = 0.0001;p=0001) and at 1 month after surgery, respectively (p = 0.0001;p=0001). Despite the relative expression of miRNA–125b and miRNA–142–3p were decreased 1.75- and 2.4-fold, respectively at 1 month after surgery, we observed no significant differences in the relative expression of miRNA–125b and miRNA–142–3p between before surgery and at 1 month after surgery, respectively (p = 0.110; p = 0.910). Bioinformatic analyses of three databases showed that miRNA–142–3p expression levels were found to be closely associated with fifty-seven genes. Among these target genes, CFL2, RGL2, WASL, CRK, BNC2, CLOCK, TGFBR1, CIITA and ZNF217 were found to be associated with endometriosis. Whereas, no target gene were observed to be associated with miRNA–125b expression in common with these three databases. The ROC curves showed that the expression of miRNA–125b and microRNA–142–3p had an area under the ROC curve (AUC) of 0.77 (sensitivity 61.9%, specificity 88.1% (0.0001;95%CI 0.65–0.90)) and AUC of 0.71 (sensitivity 52.4%, specificity 73.8% (p < 0.007;95%CI 0.58–0.84)) before surgery, respectively. Correlational analysis showed a significant positive correlation between miRNA–142–3p and Hemoglobin A1c (Spearman's correlation, r = 0.507;p=0.019) in the endometriosis group. Limitations, reasons for caution: Further studies are needed to examine the expression of these miRs with a long-term follow up in order to increase their usefulness as a predictor in the clinical practice. It is required to identify the expressions levels of predicted target genes which are associated with endometriosis and regulated by miRNA–142–3p. Wider implications of the findings: Findings suggest that the over-expression of miRNA–125b and miRNA–142–3p may be potential mechanisms involved in the etiopathogenesis of endometriosis which is a systemic chronic inflammatory disease. We observed that miRNA–125b may be a more reliable biomarker than miRNA–142–3 for noninvasive diagnosis of endometriosis and even follow-up of women with endometriosis. Trial registration number: 118S298